MODIFIED WIENER–HOPF EQUATION IN IDENTIFICATION PROBLEMS - Afanasyev, Valeriy; Titov, Dmitry Vitalievich (Journal of Applied Engineering Science, 2018)
The method of adaptive filtration in the tasks of flow settings of cosmic radiation recovery by the measured data for the use in cosmic transport systems with a long life cycle was shown in the article. The mathematic model and algorithm of optimization of non-stationary control systems, in which the measurement condition is doing during the noise, are described. Algorithms of parametric optimization are done by the use of modified Wiener-Hopf equation and systems of sensitivity.